A case of intracranial solitary fibrous tumor/hemangiopericytoma with dedifferentiated component. Issue 3 (16th December 2014) - Maekawa, Akira; Kohashi, Kenichi; Yamada, Yuichi; Nakamizo, Akira; Yoshimoto, Koji; Mizoguchi, Masahiro; Iwaki, Toru; Oda, Yoshinao
<x xml:space="preserve">Abstract</x> We report the case of a 51‐year‐old Japanese man with an intracranial dedifferentiated solitary fibrous tumor/hemangiopericytoma (SFT/HPC) identified morphologically and immunohistochemically, comprised of a typical SFT/HPC with a high‐grade pleomorphic component. NAB2‐STAT6 fusion transcripts were detected by reverse transcriptase polymerase chain reaction in both the conventional and high‐grade components. The tumor cells in both components showed the nuclear expression of STAT6 protein, indicating the diagnostic value of these examinations. Intracranial dedifferentiated SFT/HPC is a very rare but important differential diagnosis in intracranial pleomorphic tumors.